Observation of Complex Time Structures in the Cosmic-Ray Electron and Positron Fluxes with the Alpha Magnetic Spectrometer on the International Space Station - Aguilar M (AMER PHYSICAL SOC, 2025)
We present high-statistics, precision measurements of the detailed time and energy dependence of the primary cosmic-ray electron flux and positron flux over 79 Bartels rotations from May 2011 to May 2017 in the energy range from 1 to 50 GeV. For the first time, the charge-sign dependent modulation during solar maximum has been investigated in detail by leptons alone. Based on 23.5 x 10(6) events, we report the observation of short-term structures on the timescale of months coincident in both the electron flux and the positron flux. These structures are not visible in the e(+)/e(-) flux ratio. The precision measurements across the solar polarity reversal show that the ratio exhibits a smooth transition over 830 +/- 30 days from one value to another. The midpoint of the transition shows an energy dependent delay relative to the reversal and changes by 260 +/- 30 days from 1 to 6 GeV.